Adquisición de datos para un sistema de medición de la calidad del aire basado en IoT (2019)
The objective of the article is to present the design of the interface for the acquisition of data from the climatological station located in Guaymaral (latitude: 04º49'20.4""N, Longitude: 74º04'10.2""W; 2585 masl). This work is part of the research project ""Measurement of local air quality, through an IoT system and advanced data analytics"", funded by the Colombian School of Engineering JULIO GARAVITO (Colombia). The methodology begins with the request of the data of the meteorological variables by the WIFI module and through the UART, to the server of the District Secretary of the Environment of Bogotá (http://201.245.192.252:81/StationInfo.aspx? ST_ID = 8), in Forward SDA. The received HTML file is saved in RESWIFI, and it is processed in order to debug the essential information of the variables. This information is then sent, via serial interface, to the node of the LoRaWAN network. The results of the design of the interface allowed to receive information of the variables particulate material (PM10 and PM2.5), speed and direction of the wind (Vel10M and Dir10M), temperature (T2m, T8m and T20m), relative humidity of the environment (RH), atmospheric barometric pressure (PB), solar radiation (RS), precipitation, ozone (O3), nitrogen monoxide (NO) and nitrogen oxides (NOX), with which the historical behavior of three of them was graphed: PM10, O3 and nitrogen dioxide (NO2), which are air pollutants.